2008
DOI: 10.1590/s0066-782x2008000100008
|View full text |Cite
|
Sign up to set email alerts
|

Revisão dos critérios de Sokolow-Lyon-Rappaport e cornell para hipertrofia do ventrículo esquerdo

Abstract: SummaryBackground: Electrocardiographically-detected left ventricular hypertrophy (LVH) is a strong predictor of cardiovascular morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
6
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 32 publications
4
6
0
Order By: Relevance
“…Many studies have shown the sensitivity of this criterion is low, and it is perplexing that the Sokolow–Lyon’s LVH criterion continues to be used in the clinical evaluation of patients, especially in the developing world with limited resources for more advanced evaluations. Rodrigues et al in 2008 showed the classic Sokolow–Lyon Rappaport and Cornell Voltage criteria showed a low performance in relation to LVH, as confirmed by ECHO,33 our results support these findings as only 4 out of the 15 participants with LVH by Sokolow–Lyons criteria had confirmed LVH by echocardiography.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Many studies have shown the sensitivity of this criterion is low, and it is perplexing that the Sokolow–Lyon’s LVH criterion continues to be used in the clinical evaluation of patients, especially in the developing world with limited resources for more advanced evaluations. Rodrigues et al in 2008 showed the classic Sokolow–Lyon Rappaport and Cornell Voltage criteria showed a low performance in relation to LVH, as confirmed by ECHO,33 our results support these findings as only 4 out of the 15 participants with LVH by Sokolow–Lyons criteria had confirmed LVH by echocardiography.…”
Section: Discussionsupporting
confidence: 89%
“…Cornell voltage criterion is less vulnerable to such factors 33. In our setting based on a higher Pearson’s correlation (Sokolow–Lyon r = 0.366, Cornell r = 0.618), we provide further support for this position.…”
Section: Discussionsupporting
confidence: 65%
“…Cornell criterion had an overall better performance especially in females. Rodrigues et al reported a similar finding [14].…”
Section: Discussionmentioning
confidence: 55%
“…Dada et al reported a high test performance in a neighboring community [8]. The poor performance of the ECG in detecting LVH has been shown in several studies [4], [12], [13], [14].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation